2023
DOI: 10.7150/ijbs.82855
|View full text |Cite
|
Sign up to set email alerts
|

SCF/c-Kit-activated signaling and angiogenesis require Gαi1 and Gαi3

Abstract: The stem cell factor (SCF) binds to c-Kit in endothelial cells, thus activating downstream signaling and angiogenesis. Herein, we examined the role of G protein subunit alpha inhibitory (Gαi) proteins in this process. In MEFs and HUVECs, Gαi1/3 was associated with SCF-activated c-Kit, promoting c-Kit endocytosis, and binding of key adaptor proteins, subsequently transducing downstream signaling. SCF-induced Akt-mTOR and Erk activation was robustly attenuated by Gαi1/3 silencing or knockout (KO), or due to domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 56 publications
(147 reference statements)
0
17
0
Order By: Relevance
“…A previous study demonstrated the crucial role of YME1L within glioma cells in facilitating the transcription and expression of G protein subunit alpha i1 (Gαi1) [ 27 ], a key protein essential for the activation of Akt-mTOR cascade through various receptor tyrosine kinases (RTKs) and non-RTK receptors [ 38 , 39 , 44 51 ]. We revealed that the suppression of YME1L, achieved through shYME1L-seq1 or shYME1L-seq2, markedly downregulated both mRNA and protein levels of Gαi1 in pOS-1 primary cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study demonstrated the crucial role of YME1L within glioma cells in facilitating the transcription and expression of G protein subunit alpha i1 (Gαi1) [ 27 ], a key protein essential for the activation of Akt-mTOR cascade through various receptor tyrosine kinases (RTKs) and non-RTK receptors [ 38 , 39 , 44 51 ]. We revealed that the suppression of YME1L, achieved through shYME1L-seq1 or shYME1L-seq2, markedly downregulated both mRNA and protein levels of Gαi1 in pOS-1 primary cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7H ). Crucially, in pOS-1 cells expressing shYME1L-seq1, the augmentation of Gαi1 expression via a lentiviral Gαi1-expressing construct (“oeGαi1”, from Dr. Cao [ 38 , 39 ]) reinstated the phosphorylation of Akt and S6K (Fig. 7I ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of SCF/c-KIT system activation in angiogenesis has been associated with the canonical mechanisms of endothelial sprouting in normal and pathological conditions [51,52]. Herein, we investigated cell distribution and immunolocalization of the c-KIT receptor to unveil its possible involvement in 'alternative' pro-angiogenic signaling pathways associated with 'unconventional' pericyte-TNT-driven vessel sprouts to promote endothelial proliferation, migration, and lumenization.…”
Section: C-kit and Pericyte-tnt-driven Vessel Sproutingmentioning
confidence: 99%